Influence of factor XIII activity on post-operative transfusion in congenital cardiac surgery-A retrospective analysis - Fahlbusch, Fabian B.; Heinlein, Thomas; Rauh, Manfred; Dittrich, Sven; Cesnjevar, Robert; Moosmann, Julia; Nadal, Jennifer; Schmid, Matthias; Münch, Frank; Schroth, Michael; Rascher, Wolfgang; Topf, Hans-Georg (PLoS ONE, 2018)
OBJECTIVES: Coagulation factor XIII (FXIII) plays a key role in fibrin clot stabilization-an essential process for wound healing following cardiothoracic surgery. However, FXIII deficiency as a risk for post-operative bleeding in pediatric cardiac surgery involving cardiopulmonary bypass (CPB) for congenital heart disease (CHD) is controversially discussed. Thus, as primary outcome measures, we analyzed the association of pre-operative FXIII activity and post-operative chest tube drainage (CTD) loss with transfusion requirements post-operatively. Secondary outcomes included the influence of cyanosis and sex on transfusion. METHODS: Our retrospective analysis (2009-2010) encompassed a single center series of 76 cardio-surgical cases with CPB (0-17 years, mean age 5.61 years) that were post-operatively admitted to our pediatric intensive care unit (PICU). The observational period was 48 hours after cardiac surgery. Blood cell counts and coagulation status, including FXIII activity were routinely performed pre- and post-operatively. The administered amount of blood products and volume expanders was recorded electronically, along with the amount of CTD loss. Uni- and multivariate logistic regression analysis was performed to calculate the associations (odds ratios) of variables with post-operative transfusion needs. RESULTS: FXIII activities remained stable following CPB surgery. There was no association of pre- and post-operative FXIII activities and transfusion of blood products or volume expanders in the first 48 hours after surgery. Similarly, FXIII showed no association with CTD loss. Cyanosis and female sex were associated with transfusion rates. CONCLUSIONS: Although essentially involved in wound healing and clotting after surgery, FXIII activity does not serve as a valid predictor of post-operative transfusion need.
EVALuna2:35481